IDENTIFICATION OF CONSEQUENTIAL PRODUCT SOUND IMPRESSION ON WOOD MECHANICAL TOY CAR PRODUCTS DESIGN POWERED BY RUBBER BRACELETS - Samuel Aswin Moeljanto; Adhi Nugraha; Andar Bagus Sriwarno (Ide dan Dialog Desain Indonesia (Idealog), 2021)
Product Sound design has been an integral part for many renown company in designing product, due to its big contribution in shaping the user's experience (Langeveld, van Egmond, Reinier; dan Özcan (2013)). According to what cause the sound, consequential product sound is the product sound that happens because of the product's internal mechanical interaction, and the charachters are dependent on the material, size, and mechanism. However, there are stillvery few people who develop and apply these principles for products made of natural material, such as wood. Whereas, by understanding the product sound produced by the wooden product, there could be a unique user experience, that in turn, will increase the product's economical value. That's why, we try to identifies the percieved product sound that may be produced on a rubber band powered mechanical toy car made of plywood as a pilot research in defining the product sound charachter of wooden toy made fromplywood. In the next research, some sound charachter concluded in this paper could be a reference and a starting point in determining the desired product sound outcu\ome. The sound identification was done on 4 test product with different mechanism, yet same basic looks. The identification include the physical sound charachter (difference in intensity, frequency, and waveform) and the perceived sound charachter (using semantic diferential). The unique perceived sound charachter found are then connected to the physical sound charachter as a general conclusion. Keywords: Product Sound Design; Wooden Mechanical Toys; Consequential Product Sound; Wooden Toys